HYBRID FLOWSHOP 2 STAGE WITH HEURISTIC METHODE - Anwar, Asep; Maharani Suyono, Anisa (International Journal of Psychosocial Rehabilitation, 2020)
PT XX is an aircraft company. The company is currently developing a scheduling method for spare parts that are processed in the miling and lathe departments, where at each work station there are 2 machines each installed in parallel. The process is the same as the understanding of the production system of the Hybrid Flowshop model, so that one solution can use a heuristic method. The number of jobs that are in this paper is 10 jobs. The purpose of this research is how to schedule these jobs to be processed in the existing production system so as to makespan minimization. After scheduling with the heuristic method, the makespan is 995 units of time.